Initial Ability of Students' Science Literacy on Optical Material in Senior High School - SUSANTI, MERI; Sari, Silvi Yulia (Universitas Negeri Padang, 2023)
Science literacy is one of the keys to facing the development of today's era. The importance of science literacy ability makes Indonesia take part in assessments conducted by international institutions. Based on the report of the international study conducted by PISA, it shows that the science literacy of students in Indonesia is still low and still far from the average international score. The purpose of this study was to determine the initial ability of students' science literacy on the material of optical devices in senior high school. This research used a descriptive method with a quantitative approach with a sample of 31 students in senior high school. The results of this study indicate that the average value of students' science literacy in the aspects of context, competence, and knowledge aspects is still low. The results of the context aspect research on personal, local, and global indicators obtained average scores of 47.75, 18.27, and 25.68. While the competency aspect on indicators of explaining scientific phenomena, evaluating and designing research, and interpreting data and scientific evidence obtained an average value of 28.57, 32.04, and 29.08, while the knowledge aspect on content, procedural, and epistemic indicators obtained an average value of 42.67, 32, and 16.53. Thus, there is a need for learning designs that apply science knowledge in life that can improve science literacy ability and assessment instruments to evaluate related science literacy ability.